Drivers of Fungal Succession in Three Different Woody Species in a Tropical Forest Fragment - Pires, Ricardo Matheus [UNESP]; Schigel, Dmitry; Kjller, Rasmus; Frslev, Tobias Guldberg; Santos, Susana Silva; Milagres, Adriane Maria Ferreira; Armani, Gustavo; de Mello Gugliotta, Adriana (Museum National d'Histoire Naturelle, Paris, France, 2025)
Wood-inhabiting fungi are important in forest ecosystems and play an essential role in nutrient and carbon recycling. However, the drivers of fungal succession are poorly understood. We assessed the fungal succession of three tree species in a fragment of Atlantic forest in the state of So Paulo, Brazil. Decomposing branches from different locations were sampled every four months for two years. This study identified 2 309 Operational Taxonomic Units (OTUs), predominantly from the phyla Ascomycota and Basidiomycota, in freshly cut branch fragments of tropical angiosperm trees. The richness exceeded comparable studies in non-tropical ecosystems, attributed to the unique substrate and sequencing methodology. Despite variations in OTU abundance across time points, no significant differences were observed between the three tree species studied. Decomposition rates exhibited temporal variations, with more intense activity during summer and reduced rates in winter. Nitrogen content increased over time, associated with microbial action. Cellulose degradation predominated, followed by hemicelluloses and lignin. Fungal community structure showed a shift from Ascomycota to Basidiomycota, indicative of a natural decomposition pattern. Factors influencing decomposition included substrate specificity, individual branch history, and the fungal community's resilience and competitiveness. The study emphasizes the complex interplay between biotic and abiotic factors in shaping fungal communities during wood decomposition in tropical forests. Overall, the findings contribute to understanding the intricate dynamics of fungal succession, nutrient cycling, and substrate specificity in tropical wood decay processes. Facteurs de succession fongique chez trois espces ligneuses diffrentes dans un fragment de fort tropicale. Les champignons vivant dans le bois sont importants dans les cosystmes forestiers et jouent un rle essentiel dans le recyclage des nutriments et du carbone. Cependant, les facteurs responsables de la succession fongique sont mal compris. Nous avons valu la succession fongique de trois espces d'arbres dans un fragment de fort atlantique de l'tat de So Paulo, Brsil. Des branches en dcomposition provenant de diffrents endroits ont t chantillonnes tous les quatre mois pendant deux ans. Cette tude a identifi 2 309 units taxonomiques oprationnelles (OTU), principalement issues des phyla Ascomycota et Basidiomycota, dans des fragments de branches frachement coupes d'angiospermes tropicaux. La richesse a dpass les tudes comparables dans les cosystmes non tropicaux, attribue au substrat unique et la mthodologie de squenage. Malgr les variations de l'abondance de l'OTU au fil du temps, aucune diffrence significative n'a t observe entre les trois espces d'arbres tudies. Les taux de dcomposition prsentaient des variations temporelles, avec une activit plus intense en t et des taux rduits en hiver. La teneur en azote a augment avec le temps, associe l'action microbienne. La dgradation de la cellulose prdominait, suivie par les hmicelluloses et la lignine. La structure de la communaut fongique a montr un changement d'Ascomycota vers Basidiomycota, indiquant un modle de dcomposition naturelle. Les facteurs influenant la dcomposition comprenaient la spcificit du substrat, l'histoire de chaque branche ainsi que la rsilience et la comptitivit de la communaut fongique. L'tude met l'accent sur l'interaction complexe entre les facteurs biotiques et abiotiques dans la formation des communauts fongiques lors de la dcomposition du bois dans les forts tropicales. Dans l'ensemble, les rsultats contribuent comprendre la dynamique complexe de la succession fongique, du cycle des nutriments et de la spcificit du substrat dans les processus de dcomposition du bois tropical.